2014
DOI: 10.1161/circulationaha.113.003312
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Injury After Neonatal Cardiac Surgery

Abstract: S urvival after neonatal cardiac surgery has improved over the past decades to >90% because of major advances in surgical techniques and perioperative management. However, it has also become evident that neurodevelopment is impaired in approximately one third of children who underwent surgery at a neonatal age.1 As seen on magnetic resonance imaging (MRI), 23% to 40% of neonates presenting with a complex cardiac defect already have evidence of cerebral injury preoperatively.2-6 After surgery, 36% to 73% of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(69 citation statements)
references
References 32 publications
1
66
0
2
Order By: Relevance
“…As recently published, we found new postoperative MRI injury in 55 % of patients, and at 2 years of age (n = 32), three patients had cerebral palsy, one had a mild motor delay (total motor delay of 13 %) and two had a cognitive delay (6 %) [3].…”
supporting
confidence: 67%
“…As recently published, we found new postoperative MRI injury in 55 % of patients, and at 2 years of age (n = 32), three patients had cerebral palsy, one had a mild motor delay (total motor delay of 13 %) and two had a cognitive delay (6 %) [3].…”
supporting
confidence: 67%
“…In a high percentage of the cardiac patients, both preoperative and de novo postoperative brain damage were visible on MRI. 8,9 These lesions could contribute to the risk of adverse neurodevelopmental outcome. The mechanism and factors increasing the risk of neurodevelopmental delay in NCCA remain unknown.…”
mentioning
confidence: 99%
“…If the blood flow is vertical to the ultrasonic waves, a movement of blood cannot be detected. It remains unclear whether our results can be extrapolated to other RCP strategies including "real" pH-stat regime and deep hypothermia (10,12,14,15,19,22,34). A superiority to other modes of RCP or neuroprotective strategies as deep hypothermic circulatory arrest cannot be derived from our experience to date, but may become likely when gathering data from an increasing number of patients.…”
Section: Discussionmentioning
confidence: 94%
“…Goal-directed-perfusion in neonatal aortic arch surgery outcome (10,11). Several studies suggested that longer duration of deep hypothermic circulatory arrest is associated with neurocognitive impairment (12)(13)(14), but despite the missing evidence of a clear time limit (12,15), perioperative seizures with impaired motor development (16) and brain damage evident on MRI were consistent with RCP as well (10,17,18).…”
Section: Review Articlementioning
confidence: 99%
See 1 more Smart Citation